The effect of opioid-sparing anesthesia regimen on short-term cognitive function after thoracoscopic surgery: a prospective cohort study - Hong Zhao; Qiaoyu Han; Chuan Shi; Yi Feng (Perioperative Medicine, 2022)
Abstract Background As type of surgery and opioids are suggested risk factors for the development of cognitive decline after surgery, we evaluated the effect of an opioid-sparing anesthesia regimen involving preoperative erector spinae block and continuous infusion of flurbiprofen on the incidence of cognitive decline after video-assisted thoracoscopic surgery. Methods In this observational study, patients over 18 years old presenting for elective video-assisted thoracoscopic surgery were divided into two groups, the erector spinae plane block group (ESPB group, who received preoperative single shot of bi-level ESPB at T4 and T6 levels) and the control group who received intercostal nerve blocks through T5 to T7 intercostal spaces along mid-axillary line after surgery. Continuous infusion of flurbiprofen (8 mg/h) and intravenous oxycodone rescue (1 mg/bolus, lockout time 10 minutes) were provided as postoperative analgesics. Cognitive function was measured one day before and 48 h after surgery with brief Cogstate computerized battery (CCB). Results There were 60 patients included with 30 in each group. Perioperative sufentanil dose was significantly reduced in ESPB group. Nine (30%) and 15 (50%) patients had delayed neurocognitive recovery in the ESPB group and the control group respectively. Psychomotor speed and visual attention tests were the two tests that patients showed cognitive decline. The results of multivariate regression revealed that patients who were more than 53.5 years of age (OR 9.213, 95% CI 1.789, 47.437, P = 0.008) and low levels of education (less than 9 years of complimentary education) (OR 6.829, 95% CI 1.068, 43.677, P = 0.042) were independent risk factors for postoperative delayed neurocognitive recovery. For subgroup analysis, ESPB could reduce the occurrence of delayed neurocognitive recovery in patients with both risk factors (6/10 (60%) vs. 11/11 (100%), P = 0.004) compared to the control group. Conclusions Middle-aged people and low levels of education are independent risk factors for delayed neurocognitive recovery after thoracoscopic surgery. ESPB has the potential to prevent cognitive decline in high-risk patients. Trial registration ChiCTR1800014508 ( www.chictr.org.cn , January 17, 2018; Hong Zhao, M.D.). URL: http://www.chictr.org.cn/showproj.aspx?proj=24778 . The date of the enrolment of the first participant to the trial was January 22, 2018.